A just compensation for leaving it in the ground: Climate easements and oil development. Issue 112 (October 2020) - Snyder, Brian F.; Ruyle, Leslie E.
Highlights: The Paris agreement implies that some fossil fuel resources must not be extracted. Foreclosed resources may be in developing nations and foreclosure may be unjust. A test is proposed to identify foreclosed resources and assign responsibility. A climate-easement approach is proposed to compensate for resource foreclosure. Abstract: The Paris Climate agreement of 2015 implies that a large portion of the world's coal, oil, and gas resources must be left non-combusted in order to meet the goal of limiting climate change to 2 °C. As a result of this commitment, some of the national and corporate owners of fossil fuel reserves will be required to leave their reserves in the ground. However, which reserves should be left in the ground, and when and how should reserve-owners be compensated? Using the oil reserves in Uganda's Albertine Graben as a case study, we show that Ugandan oil development is likely to be cost-effective but unlikely to be consistent with the Paris Treaty commitments. We argue that Western nations should compensate Uganda for their foregone oil revenues and we propose a mechanism called "climate easements" for such compensation.